Plantão psicológico no Brasil (1997-2009): saberes e práticas compartilhados - SOUZA, Bianca Nascimento de (2011)
The purpose of this study was to investigate scientific production on Emergency Psychological Services in Brazil between 1997 and 2009 by trawling scientific, electronic databases, using the descriptor Emergency Psychological Services. Thirty-eight abstracts were obtained, analyzed based on the following categories: distribution, authorship, institutional affiliation, source, year, publication support, target population, theoretical approach, nature of work and geographic region of the country. The results suggest that the electronic databases are currently an important source of access to production on Emergency Psychological Services in Brazil. It is in the southeast where we see a prevalence in production on this subject, as well as the use of the Person-Centered Approach, revealing a greater emphasis on research related to dissertations, with the greatest level of production being noted in 2005 and 2006.